Momentum strategies and market state in Moroccan industries - Omar K. Gharaibeh; Buthiena Kharabsheh; Ali Z. Al-Quran (Cogent Business & Management, 2022)
This study aims to examine whether there is any evidence of momentum in Moroccan industries and whether these momentum returns are attributed to the market status, UP and Down based on monthly data from December 1997 to December 2019. The portfolio methodology was used to classify 17 Moroccan industries within four portfolios; each portfolio constitutes 25% of Moroccan industries. The 3-factor model of Fama and French was employed to consider the risk-adjusted returns. The results showed that there is ample evidence and statistically significant momentum returns in Moroccan industries. The sub-sample findings support the evidence of momentum. This study also shows that momentum returns in the Moroccan industry are not exclusive to the UP or DOWN market because momentum returns are present in both "Up" and "Down" markets. These results are important for investors to design their investment strategies and take advantage of the momentum returns in Moroccan industries. This study contradicts the efficient market hypothesis because of the inability of the Fama-French 3-factor model to account for momentum profits; therefore, the paper recommends using the Fama-French five-factor model.
Keywords: G14; G15; 650; market status; momentum; Morocco